The Impact of Open Selection on the Number of Corruption Cases in High Leadership Positions (JPT) in Local Governments in Indonesia - Winda Hestiecia (Jurnal Magister Administrasi Publik, 2021)
This study aims to explain the impact of implementing open selection on the amount of corruption in local government JPT in Indonesia. Using the difference-in-differences-in-differences (DDD) approach, this study analyzes panel data on JPT corruption in Indonesia that have been inkracht handled by the Corruption Eradication Commission (KPK) in the period 2009-2019. The results of theoretical studies and previous research have given rise to the hypothesis that the implementation of open selection has a positive impact on reducing JPT corruption cases in local governments in Indonesia. This study found that the implementation of open selection can reduce the number of corruption cases by -0.892% and significantly at the 10% alpha level in regions with high total capital expenditures. This finding demonstrates the positive impact of open selection on JPT corruption cases and thus supports previous studies on the positive impact of implementing a merit system, in particular open selection on the number of JPT corruption cases in regions with high total spending. In addition, to strengthen the research results by adding case studies and in-depth interviews with KASN and ICW. It was found that it greatly influenced the implementation of open selection. It is the high political costs in the regions that are the main cause that causes corruption of governors, mayors, and regents followed by regional officials to continue to occur.